Diet dan Sindrom Metabolik pada Remaja Obesitas - Rendi Aji Prihaningtyas; Nur Aisiyah Widjaja; Meta Herdiana Hanindita; Roedi Irawan (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2020)
ABSTRACTBackground : The prevalence of obesity in adolescents is increasing and causes metabolic syndrome at a young age. Metabolic syndrome results from the interaction of environmental, genetic, and dietary factors. The purpose of this study was to determine the diet profile of obese adolescents suffering from metabolic syndrome.Methods: This study was a cross-sectional study of obese adolescents who visited the Pediatric Nutrition and Metabolic Disease in Dr. Soetomo General Hospital, Surabaya. The anthropometry examination (weight, height and waist circumference), blood pressure, and blood tests (HDL cholesterol, triglycerides and blood glucose levels) were measured. The diagnosis of metabolic syndrome was based on the International Diabetes Federation. Food consumption data was obtained through direct interviews using data collection sheets. Analysis of dietary differences in obese adolescents suffering from metabolic syndrome was performed by chi square using SPSS.Results and Discussions: A total of 59 obese adolescents aged 13-16 years were involved in this study. A total of 27 subjects (45.8%) suffered from metabolic syndrome and 32 subjects (54.2%) did not suffer from metabolic syndrome. The level of the consumption of fish, vegetables, and fruit in obese adolescents were still low. There was no significant difference in the diet profile between obese adolescents who suffer from metabolic syndrome or not.Conclusion: Prevention strategies through food consumption patterns are needed in obese adolescents to control metabolic stress processes and prevent metabolic syndrome in the future. Diet knowledge in obese adolescents needs to be given early to prevent further complications. Increasing foods that contain anti-oxidants, such as fruits and vegetables, is one of the strategies to prevent metabolic syndrome in obese adolescents.ABSTRAKLatar Belakang : Prevalensi obesitas pada remaja semakin meningkat dan menyebabkan sindrom metabolik di usia muda. Sindrom metabolik terjadi akibat interaksi faktor lingkungan, genetik, dan diet. Tujuan dari penelitian ini adalah mengetahui profil diet pada remaja obesitas yang menderita sindrom metabolik.Metode : Penelitian ini merupakan penelitian potong lintang pada remaja obesitas yang berkunjung di Poli Nutrisi dan Penyakit Metabolik Anak di RSUD Dr. Soetomo, Surabaya. Pada subyek dilakukan pemeriksaan antropometri (berat badan, tinggi badan, dan lingkar pinggang), pemeriksaan tekanan darah, dan pemeriksaan darah (kolesterol HDL, trigliserida, dan kadar glukosa darah). Diagnosis sindrom metabolik ditegakkan berdasarkan International Diabetes Federation. Data konsumsi makanan didapatkan melalui wawancara langsung dengan menggunakan lembar pengumpul data. Analisis perbedaan diet pada remaja obesitas yang menderita sindrom metabolik dilakukan dengan chi square menggunakan SPSS.Hasil dan Pembahasan : Sebanyak 59 remaja obesitas yang berusia 13-16 tahun terlibat dalam penelitian ini. Sebanyak 27 subyek (45,8%) menderita sindrom metabolik dan sebanyak 32 subyek (54,2%) tidak menderita sindrom metabolik. Tingkat konsumsi ikan, sayur, dan buah pada remaja obesitas masih rendah. Tidak ada perbedaan yang bermakna pada profil diet antara remaja obesitas yang menderita sindrom metabolik maupun tidak.Kesimpulan : Strategi pencegahan melalui pola konsumsi makanan diperlukan pada remaja obesitas untuk mengontrol proses stres metabolik sehingga dapat mencegah sindrom metabolik di masa datang. Pengetahuan diet pada remaja obesitas perlu diberikan sejak dini untuk mencegah komplikasi lebih lanjut. Memperbanyak makanan yang mengandung anti-oksidan, seperti buah dan sayur merupakan salah satu strategi mencegah sindrom metabolik pada remaja obesitas.